Phytochemical Screening and Effects of Parquetina Lemongrass Herbal Tea on Haematological, Serum Biochemical and Histological Parameters in Wistar Rats - Victoria Joshua; Rowland Kayode; Mayowa Sanusi; Aderinola Awoniyi; Olufunmilola Abiodun; Bukola Kayode (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and objectives. Herbal teas are beginning to gain more attraction globally due to their ability to promote health and well-being by virtue of the bioactive compounds in them. This attraction is fostered by consumers’ interests in foods that go beyond basic nutrition to provide certain health benefits. This study investigated the effect of a composite herbal tea from Parquetina and Lemongrass on health. Methods. Infusions of five different formulations of Parquetina and Lemongrass at 100:0%, 87.5:12.5%, 75:25%, 62.5:37.5% and 50:50%, were analyzed for their impact on the health of Wistar rats using water as a control. Results. The Wistar rats fed on different formulations of the composite herbal tea showed significant (P≤0.05) decrease in body weight, blood urea nitrogen, creatinine, alanine transaminase, alanine aspartate, triglycerides, cholesterol, low-density lipoprotein and glucose when compared with control group fed with water. Packed cell volume, red blood cells and haemoglobin levels were significantly (P≤0.05) increased, while high-density lipoprotein, total protein and feed intake remained unaffected. Histological examinations of the liver and kidney showed no evidence of toxicity. More so, there was no mortality recorded during the period of the study. Conclusion. The findings of this study reveal that parquetina-lemongrass herbal tea has the potential of improving health evidenced by its erythropoietic, anti-diabetic and anti-cholesteremic properties, and its ability to maintain normal liver and kidney functions.